2018
DOI: 10.1038/s41598-018-20322-3
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year field study showed no apparent effect of the Bt transgenic 741 poplar on the arthropod community and soil bacterial diversity

Abstract: China is currently the only country that has commercialized genetically engineered tree species, and this has attracted worldwide attention. As a perennial tree species, transgenic poplar has a long growth cycle and needs to be tested for long-term ecological risks. The main purpose of this study was to explore the ecological safety of perennial transgenic poplars in arthropod community, physical and chemical properties of soil, gene flow, and soil microbial diversity. The study found transgenic poplars could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Our lab is associated with the area of research on biotechnological interventions in T. chebula for rapid multiplication of this important medicinal tree for forestry (Shyamkumar et al, 2003;Anjaneyulu et al, 2008;Shyamkumar and Giri 2011;Anjaneyulu and Giri 2011). There has been a constant need to develop protocols for genetic transformation in tree species in general and T. chebula in particular for genetic improvement (Giri et al, 2004;Shyamkumar et al, 2007;Dangi et al, 2012;Verma et al, 2013;Zuo et al, 2018). In the present communication, we report biochemical analysis and genetic transformation studies using somatic embryogenesis culture system of T. chebula.…”
Section: Introductionmentioning
confidence: 79%
“…Our lab is associated with the area of research on biotechnological interventions in T. chebula for rapid multiplication of this important medicinal tree for forestry (Shyamkumar et al, 2003;Anjaneyulu et al, 2008;Shyamkumar and Giri 2011;Anjaneyulu and Giri 2011). There has been a constant need to develop protocols for genetic transformation in tree species in general and T. chebula in particular for genetic improvement (Giri et al, 2004;Shyamkumar et al, 2007;Dangi et al, 2012;Verma et al, 2013;Zuo et al, 2018). In the present communication, we report biochemical analysis and genetic transformation studies using somatic embryogenesis culture system of T. chebula.…”
Section: Introductionmentioning
confidence: 79%
“…The dominant insect species in all poplars was Hemiptera, followed by Lepidoptera, Homoptera, Araneida, and Diptera, whereas numbers of Mantodea, Neuroptera, Odonata, and Acarina were relatively low. The main poplar pests (primarily Lepidoptera) were significantly inhibited in the transgenic poplars; however, the number of Coleoptera pests was generally low, and the inhibitory effect was not clear (Zuo et al, 2018). …”
Section: Biosafety Assessmentmentioning
confidence: 99%
“…Studies of the microbial diversity of 5-year-old transgenic poplar 741 showed that transgenic poplars did not affect the physical and chemical properties of the soil or the soil microbial community structure. However, the microbial community structure was obviously affected by the location and season (Zuo et al, 2018). …”
Section: Biosafety Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…deltoides (Ramachandran et al, 1993) P . euramericana (Wang et al, 1997), NL-80106 ( Populus deltoides × Populus simonii ) (Guo et al, 2004) and 741 poplar (Tian et al, 2000; Yang et al, 2003) were successfully cultivated, and there are now resources for continuously introducing new insect-resistant poplar varieties (Zuo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%